2013
DOI: 10.1111/cpf.12072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of load and type of physical training on resting and postexercise cardiac autonomic control

Abstract: The aim of the study was to investigate the influence of training load and exercise mode on heart rate variability and heart rate recovery (HRR) in healthy individuals. The subjects were divided into three groups: sedentary (SED), resistance trained (RT) and aerobically trained (RT). Resting and postmaximal exercise RR intervals were recorded on supine and seated position, respectively. The HRV indices calculated in the resting position were RMSSD and LF and HF power densities. The following HRR indices were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
2
10
0
2
Order By: Relevance
“…Our results show, in accordance to previous findings (16), faster vagal reactivation in males, perceived by T30 which is an immediate post-exercise index of vagally mediated cardiac rate decay (50,51). HRR was found to be in a strong correlation with the level of physical activity (52). It was also found to negatively correlate with resting supine parasympathetic markers of HRV when in standing position during the first minute of recovery, but the higher the indices of combined autonomic modulation were (LF, lnLF), greater was the HRR in third and fifth minute post-exercise (53).…”
Section: Discussionsupporting
confidence: 93%
“…Our results show, in accordance to previous findings (16), faster vagal reactivation in males, perceived by T30 which is an immediate post-exercise index of vagally mediated cardiac rate decay (50,51). HRR was found to be in a strong correlation with the level of physical activity (52). It was also found to negatively correlate with resting supine parasympathetic markers of HRV when in standing position during the first minute of recovery, but the higher the indices of combined autonomic modulation were (LF, lnLF), greater was the HRR in third and fifth minute post-exercise (53).…”
Section: Discussionsupporting
confidence: 93%
“…50 Whereas sedentary lifestyle, poor functional capacity, 53,54 or excessive exercise seems to increase the risk of AF, 53 the moderate exercise seems to have a protective effect and decreases the risk of AF 55 and positively influences the HRR. 56 Therefore, the modulation of ANS activity may constitute an important therapeutic strategy for the management of AF 2,57 We found that the AFCA by PVAI impaired the noninvasive ANS parameters, but this effect was not found to be associated with post-PVI AF recurrence. Complete elimination of vagal response (vagal denervation) appeared associated with reduced AF recurrence [7][8][9] and with marked HRV changes consistent with ANS withdrawal.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, highly trained athletes often display a rapid and profound drop in HR of ≥30–50 beat during the first minute of HRR from strenuous exertion . Whereas sedentary lifestyle, poor functional capacity, or excessive exercise seems to increase the risk of AF, the moderate exercise seems to have a protective effect and decreases the risk of AF and positively influences the HRR . Therefore, the modulation of ANS activity may constitute an important therapeutic strategy for the management of AF…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular fitness has been shown to influence HRR, as more fit individuals show a faster HRR than less fit individuals [20,21,42]. Thus, it is possible that poor cardiovascular fitness in young people with PWS also contributed to the compromised HR response following resistance exercise.…”
Section: Resultsmentioning
confidence: 99%